Spectre of the commons : a political economy of radio regulation in the communism of capital - O'Dwyer, Rachel (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2014)
This thesis performs a critique of the political economy of mobile networks through the theoretical framework of the communism of capital. It identifies the economic centrality of social production to the contemporary economy and analyses how the proprietary enclosure of network resources facilitates the accumulation of value from social production over mobih; networks.
Keywords: Electronic and Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin